Jeremy Chan and Hilferah Tan are Perak Amateur Champions - Golf, Malaysia (Golf Malaysia, 2012)
Jeremy Chan, who already has a PGM Tour card, and Universiti Utara Malaysia (UUM)'s undergraduate Hilferah Tan, bagged their first state amateur champions, the 2012 Perak Amateur Open, at Clearwater Sanctuary Resort in Batu Gajah Perak.